Aplikasi Isotop Alam untuk Mengetahui Asal-Usul Air Umbul Cokro, Kecamatan Tulung, Kabupaten Klaten - Harry Leo Kharisma; Agus Budhie Wijatna; Wahyu Wilopo (Faculty of Engineering, Universitas Gadjah Mada, 2015)
Determination of the goundwater origin of Umbul (spring) Cokro, at Klaten has been done by using environmental isotope tracers, i.e. carbon-13, deuterium, and oxygen-18. Groundwater samples were taken from springs and wells in surround of it, i.e. Wajong Wetan, Kemiri, Karang Podang, Sodong, and Karang Kendal. In the mean time, determination of groundwater genesis has been conducted by analyzing the composition of deuterium (2H) and oxygen-18 (18O) using mass spectrometer. While the direction of groundwater which has the same genesis is determined by analyzing of carbon-13 composition and will be verified by hydraulic gradient.If the composition of sample from suround is almost equal with sample from spring, hence groundwater from well flows to spring.The result of this research showed that δ13C composition of each sample is -12,92 + 4,20 until 5,56 + 4,31 o/oo PDB, that means that the sample include in Groundwater DissolvedInorganic Carbon; while analysis of deuterium and oxygen-18 indicated that composition of groundwater molecule in Sodong, Karang Podang, and Karang Kendal are almost equal to the spring, with δD composition = -52,00 + 0,77 o/oo and δ18O composition = -9,16 + 0,28 o/oo to Standard Mean Ocean Water (SMOW). Based on those results, groundwater of Umbul Cokro originally from Sodong, Karang Podang, and Karang Kendal.Keywords: groundwater, recharge area, Umbul Cokro, environmental isotope tracer.